Analysis of Basic Football Technical Skills Levels Using The Motion Sequence Test (David Lee Test) - Ikhwanul Arifan Arif; vega Soniawan; ardo okilanda (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This research is motivated by the fact that there are still many coaches who do not know the process of knowing the technical skill level of their athletes. So that in making training programs, many coaches generalize the training program, without knowing the skill level of the athlete. This study aims to determine the level of basic football technical skills using the test series of movement. The research population is SSB athlete Putra Wijaya, Freshwater Padang City. The instrument used was the david lee soccer potential circuit test, namely the 20 m run test, the basic technique of motion without the ball and the basic technique of motion with the ball. The analysis technique used is descriptive statistics. The results of Basic Soccer Technical Skills using the David Lee Test for SSB Athletes Putra Wijaya, Freshwater Padang City are categorized as adequate with an average time of 43.50 seconds, with details in the Very Good category as much as 7.69%, the Good category as much as 23.08%, the Enough category as much as 34.62%, in the Poor category as much as 26.92% and in the Very Poor category as much as 7.69%. Keywords: Basic Football Technical Skills